Adaptive gene profiling of Mycobacterium tuberculosis during sub-lethal kanamycin exposure. (November 2017) - Habib, Zeshan; Xu, Weize; Jamal, Muhammad; Rehman, Khaista; Dai, Jinxia; Fu, Zhen fang; Chen, Xi; Cao, Gang
Abstract: Resistance to anti-tuberculosis drugs is a formidable obstacle to effective tuberculosis (TB) treatment and prevention globally. New forms of multidrug, extensive drug and total drug resistance Mycobacterium tuberculosis ( Mtb ) causing a serious threat to human as well as animal's population. Mtb shows diverse adaptability under stress conditions especially antibiotic treatment, however underlying physiological mechanism remained elusive. In present study, we investigated Mtb' s response and adaptation with reference to gene expression during sub-lethal kanamycin exposure. Mtb were cultured under sub-lethal drug and control conditions, where half were sub-cultured every 3-days to observe serial adaptation under same conditions and the remaining were subjected to RNA-seq. We identified 98 up-regulated and 198 down-regulated responsive genes compared to control through differential analysis, of which Ra1750 and Ra3160 were the most responsive genes. In adaptive analysis, we found Ra1750, Ra3160, Ra3161, Ra3893 and Ra2492 up-regulation at early stage and gradually showed low expression levels at the later stages of drug exposure. The adaptive expression of Ra1750, Ra3160 and Ra3161 were further confirmed by real time qPCR. These results suggested that these genes contributed in Mtb 's physiological adaptation during sub-lethal kanamycin exposure. Our findings may aid to edify these potential targets for drug development against drug resistance tuberculosis.